2006
DOI: 10.3748/wjg.v12.i29.4665
|View full text |Cite
|
Sign up to set email alerts
|

Mental and physical symptoms associated with lower social support for patients with hepatitis C

Abstract: by others (19%). Nearly one fifth of the patients did not share information about their disease with others to avoid being stigmatized. Lower levels of social support were significantly associated with living alone, being unemployed, being excluded from antiviral therapy, having psychiatric comorbidities, contracting HCV through intravenous drug use, having high levels of anxiety and depression as measured by the HAD and negative mood state as measured by the SIP. Patients reporting lower levels of social supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 53 publications
(48 reference statements)
1
9
0
Order By: Relevance
“…Research has demonstrated that interpersonal relationships can be strained when individuals undergo antiviral therapy . Similar to what was found by Blasiole et al (2006), the increased anger and irritability the participant experienced during antiviral therapy had put a strain on his relationship with his spouse and friends. At times during the treatment, he isolated himself from family and friends.…”
Section: Discussionsupporting
confidence: 65%
“…Research has demonstrated that interpersonal relationships can be strained when individuals undergo antiviral therapy . Similar to what was found by Blasiole et al (2006), the increased anger and irritability the participant experienced during antiviral therapy had put a strain on his relationship with his spouse and friends. At times during the treatment, he isolated himself from family and friends.…”
Section: Discussionsupporting
confidence: 65%
“…Despite repeated educational campaigns by the NIH and other groups, up to one-fifth of healthcare providers voiced concerns about transmission of the disease through casual contacts, vertical transmission, or sharing of dishes [14,19]. Advice based on such incorrect information could further the erosion of social support if patients, who may already be shunned by family, friends, or coworkers, consider themselves a health hazard and choose to isolate themselves from others [46].…”
Section: With An Estimated 4 Million Infected Individuals In the Unitedmentioning
confidence: 99%
“…The influence of perceived social support on these variables has not been approached. However, in chronic liver diseases, such as hepatitis B or C, satisfactory support implies improved patient progress and recovery (9,10) and a decrease in the frequency and intensity of depressive symptoms (11).…”
Section: Introductionmentioning
confidence: 99%